Spatial and flat geometry: an experience with students of the II period of Early Childhood Education (Research, Society and Development, 2020)
This paper aims to discuss the teaching and learning process of spatial and flat geometry in early childhood education from the handling of geometric solid. Historically,  it appears that this teaching stage transitions between the assistentialist and pedagogical conceptions, the latter challenging because it conceives the intentionality of the educational practice requiring playfulness and expansion of cognitive knowledge. The research has a qualitative approach whose instruments were the observations and the researchers' logbook and photographic record. The results reveal that children, when manipulating geometric solids, discovered the flat figures, their properties and relationships with reality. Geometric thinking was explored in an investigative environment marked by playfulness and interactions favoring the integral development of students. The work is a contribution that brings together the teaching of geometry and early childhood education considering their singularities.